2013
DOI: 10.13172/2054-7331-1-1-924
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two transcription factors: NF-kB and HIF crosstalk

Abstract: Introduction Hypoxia-inducible factor is a key transcriptional factor involved in the cellular response to low levels of oxygen, hypoxia. Moreover, hypoxiainducible factor has been recently associated with a role in inflammation and immunity. Importantly, hypoxiainducible factor is regulated by the major inflammatory responsive transcription factor, nuclear factor-κB. These two major pathways have been intimately linked. On one hand, they share a number of common target genes; on the other hand, physical inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…One of the Ras genes, Kras was reported as a well-established target of let-7 and also demonstrated to be a part of the MAPK signaling pathway [ 51 ] Upregulated let-7 in response to CI may damage the kidney blood cells that involved in proliferation and differentiation when exposed to radiation [ 48 ]. Acute kidney injury induces NF-κB, one of the major inflammation mediators and also the transcriptional factor HIF-1 that involved in the cellular response to low level of oxygen, hypoxia [ 52 , 53 ]. Recently, the HIF-1 has been shown to play a role in inflammation, indicating that both HIF-1 and NF-κB pathways were intimately linked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the Ras genes, Kras was reported as a well-established target of let-7 and also demonstrated to be a part of the MAPK signaling pathway [ 51 ] Upregulated let-7 in response to CI may damage the kidney blood cells that involved in proliferation and differentiation when exposed to radiation [ 48 ]. Acute kidney injury induces NF-κB, one of the major inflammation mediators and also the transcriptional factor HIF-1 that involved in the cellular response to low level of oxygen, hypoxia [ 52 , 53 ]. Recently, the HIF-1 has been shown to play a role in inflammation, indicating that both HIF-1 and NF-κB pathways were intimately linked.…”
Section: Discussionmentioning
confidence: 99%
“…These two major pathways share common target genes including EPO that is produced by the kidney which regulates red blood cell production in the bone marrow as indicated in our bioinformatics analysis. Studies have also reported physical interaction between these molecules [ 53 , 54 ]. NF-kB has been shown to directly activate let-7e during osteoclast differentiation [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As part of this complex interaction, an extensive crosstalk between the two main molecular players involved, HIF (hypoxia) and NF‐κB (inflammation), has been reported. This crosstalk includes common activating stimuli, and shared regulators and targets, as recently reviewed . The hypoxia‐induced activation of the NF‐κB pathway was first reported in 1994 , and thereafter a number of studies followed to elucidate the mechanisms underlying this activation.…”
Section: Hif and Nf‐κb Crosstalkmentioning
confidence: 99%
“…In this review we will focus on the pathways described for the activation of NF-κB in hypoxia and describe the roles of NF-κB in the cellular response to low oxygen. Of note, an extensive crosstalk exists between HIF and NF-κB, which has been recently reviewed elsewhere [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%